Detritus decorations as the extended phenotype deflect avian predator attack in an orb‐web spider. (6th September 2020) - Ma, Nina; Yu, Long; Gong, Deyong; Hua, Zeyuan; Zeng, Hua; Chen, Luyao; Mao, Aijia; Chen, Zhizhao; Cai, Ruxing; Ma, Yubing; Zhang, Zengtao; Li, Daiqin; et al.
Abstract: A number of strategies that divert attacks of visually guided predators, such as birds, have evolved multiple times in animals. Detritus web decorations built by certain orb‐web spider species are thought to deflect avian predator attacks away from spiders and towards their web decorations. Still, empirical evidence for this function and its adaptive significance is lacking. The orb‐web spider, Cyclosa monticola, adorns its web using a linear detritus decoration consisting of moults, egg sacs, prey remains and leaf litters. In the present study, we investigated whether detritus decorations constructed by C. monticola spiders divert attacks of avian predators away from spiders. We first employed colour modelling to compare spider bodies and detritus decoration colouration from the perspective of domestic chicks and blue tits. We then experimentally tested the deflection hypothesis in the laboratory using naïve chicks as predators. We put the chicks in a cage containing a web either with (S+) or without (S−) a spider and either with (D+) or without (D−) detritus decoration (a total of four types of webs: S+D+, S+D−, S−D+ and S−D−) under both natural habitat background and white background. We found that the colour of C. monticola spiders is indistinguishable from that of their detritus decorations for both chicks and blue tits with both backgrounds. Laboratory predation experiments showed that with both backgrounds, chicks attacked the spiders much less frequently when their decorations were present on the webs (S+D+; natural habitat: 20%, white background: 30%) than when their decorations were absent (S+D−; natural habitat: 95%, white background: 85%), resulting in greater spider survival advantage. We also found that the rate of attack of spiders and their decorations was not random; the decorations were more likely to be attacked than spiders, regardless of the ratio of surface area of decorations to spider bodies when both spiders and decorations were presented (S+D+). Therefore, our results support a deflection, rather than concealment hypothesis for web decorations. In conclusion, our study provides evidence that the extended phenotypes beyond the animal bodies, can divert avian predator attacks, therefore, may improve the fitness of animals. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.